2018
DOI: 10.1002/adfm.201803073
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Mechanics of Helicoidal Composites through Additive Manufacturing and Beetle Developmental Stage Analysis

Abstract: Investigation into the microstructure of high performance natural materials has revealed common patterns that are pervasive across animal species. For example, the helicoid motif has gained significant interest in the biomaterials community, where recent studies have highlighted its role in enabling damage tolerance in a diverse set of animals. Moreover, the helicoid motif corresponds to a highly adaptable architecture where the control of the pitch rotation angle between fibrous structures produces large chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…Recent investigations revealed that crack twisting mode significantly enhances fracture toughness in the Bouligand architecture where a crack plane propagates following the twisted fiber orientation (27)(28)(29)(30)(31)(32)(33). This amplifies the crack surface area and reorients fibers orientation in response to external loadings (27)(28)(29)33), e.g., tension, bending, or impact loads.…”
mentioning
confidence: 99%
“…Recent investigations revealed that crack twisting mode significantly enhances fracture toughness in the Bouligand architecture where a crack plane propagates following the twisted fiber orientation (27)(28)(29)(30)(31)(32)(33). This amplifies the crack surface area and reorients fibers orientation in response to external loadings (27)(28)(29)33), e.g., tension, bending, or impact loads.…”
mentioning
confidence: 99%
“…This is related to the rotating plywood structure found in the septa (SI Appendix, Fig. S6), which has been demonstrated as a microstructure to enhance strength, damage tolerance, and toughness considerably (49)(50)(51). Moreover, the richer organic contents in the septa (8) may also improve the damage resistance (52).…”
Section: Resultsmentioning
confidence: 88%
“…These chitin-nanofibril-based natural materials are far stiffer and non-deformable compared to elasmoid fish scales (Dastjerdi and Barthelat, 2015;Quan et al, 2018;Yang et al, 2013a;Zimmermann et al, 2013). The Bouligand architecture in this type of material lead to a twisting crack front advance which serves to increase the fracture toughness primarily by crack deflection (Suksangpanya et al, 2017;Suksangpanya et al, 2018;Zaheri et al, 2018); we term these brittle Bouligand structures. Theoretical analyses of such twisted crack trajectories within these Bouligand structures have been proposed (Fischer et al, 2017;Suksangpanya et al, 2017) with the enhanced toughness attributed to the increment in crack-surface area and fracture mode-mixity.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical analyses of such twisted crack trajectories within these Bouligand structures have been proposed (Fischer et al, 2017;Suksangpanya et al, 2017) with the enhanced toughness attributed to the increment in crack-surface area and fracture mode-mixity. Recently, through the use of additive manufacturing techniques, fracture mechanisms have also been explored experimentally in fabricated biomimetic Bouligand type materials (Chen et al, 2018;Feilden et al, 2017;Suksangpanya et al, 2018;Yang et al, 2017b;Zaheri et al, 2018). Computational approaches, such as finite element methods with a pre-defined cohesive interface, have also been applied to study the phenomenon of twisted cracks in the brittle form of the Bouligand structure (Suksangpanya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%